A Comparison of Clinical and Radiological Outcomes of Different Anatomical Regions Plate osteosynthesis in Cats with Body of Ilium Fractures - Arıcan, Mustafa; Zamirbekova, N; Uzunlu, EO; Ozdil, B; Gümüş, F (Journal of the Hellenic Veterinary Medical Society, 2022)
Pelvis fractures in cats are one of the most common orthopedic problems that cause serious injuries. Pelvic fractures are between 20-32% out of all fractures in cats. Os Ilium fractures constitute 18-46% of pelvic fractures. In the presented study, the post-operative clinical and radiological results of placing the plate on the dorsal, ventral and lateral of the corpus ossis ilii in cats with os ilium fractures were evaluated. Twenty three cats (different races, ages and sex) with corpus ossis ilium and multiple fractures (sacro-iliac joint luxation, acetabulum fractures, os ischium fractures) were used as a materials. Anamnesis, clinical and neurological examinations of patients were taken and 3 groups were formed for this study. Group 1; In 7 cases, the plate was placed in the dorsal of the body of ilium, in group 2, 7 cases in the lateral of body of ilium and in Group 3; in 6 cases, in the ventral of the body of ilium. Operations were performed under general anesthesia. LC-DCP plate or reconstruction plates were used for fixation. There was no narrowing in the pelvic canal and no screw loosening in cases applied dorsally and ventrally. In 6 (85.7%) of 7 cases, there was no narrowing in the pelvic canal in lateral application. Only one case had problem. Recovery rate (85.7%) in all cases. In conclusion, in cases of os ilium fracture in cats, no difference was observed between the clinical and radiological (narrowing in the pelvic canal) results of placing LC-DCP or reconstruction plates on the dorsal, lateral and ventral of the bone in the post-operative period. Thus, screw loosening did not occur. But, case selection is important in the lateral, dorsal or ventral application of the plate in os ilium fractures. If the surgical intervention has passed 5-6 days, double plate application provides a better prognosis. Dorsale plate application provides ease of manipulation when compared to ventral application. Also, if the fracture line close to the acetabulum, lateral application should be preferred.